DEVELOPMENT OF AN ENTREPRENEURSHIP SOUL TRAINING MODEL FOR UNIVERSITAS BRAWIJAYA'S STUDENTS - Mawardi, Mukhammad Kholid; Muslim, Abdul Qadir; Setyono, Langgeng; Praja, Bayu Amengku (Faculty of Administrative Science, Universitas Brawijaya, 2024)
Human capital theory argues that if someone is given education, in the future their work productivity will develop, because someone has the knowledge and skills to carry out their work better. The nation's literacy rate has increased. Based on 2016 BPPS data, the imbalance between job opportunities and the workforce in Indonesia means that intellectual unemployment is increasing. A shift in the education system is needed, namely not producing graduates who are solely looking for job opportunities, but rather graduates who are oriented towards job creation, namely entrepreneurship and campaigning for the promotion of entrepreneurship in the PT world. Based on this, this research is very important to carry out because it will help reduce the number of educated unemployed, especially in the UB Vocational Faculty. Graduates do not only choose to become civil servants and formal jobs, but can become entrepreneurs to build the nation and state. Therefore, the researchers took the title